Chapter Self-examination, Understanding, Transmission: On Becoming a Teacher in Clauberg's Logica vetus et nova - Efal-Lautenschlaeger, Adi (Knowledge and its Histories, 2023)
This paper takes a fresh look at Johannes Clauberg's Logica vetus et nova, in order to try to clarify its nature and character. Differently from prior readings of Clauberg that analyze his philosophy from the point of view of the construction of 'ontology', the approach of the present paper sees in Clauberg's philosophy a late-Humanist work, accentuating his pedagogic and hermeneutical interests. Indeed, in Clauberg's philosophy, hermeneutics and pedagogy are intrinsically bound together. This, the paper suggests, is supported not only by the concrete subject-matters of his logic, but also by the examination of Clauberg's milieu and of his sources. Analysis, in this framework, has a strictly hermeneutical usage.